2023
DOI: 10.1167/iovs.64.2.18
|View full text |Cite
|
Sign up to set email alerts
|

Familial Exudative Vitreoretinopathy and Systemic Abnormalities in Patients With CTNNB1 Mutations

Abstract: Purpose Familial exudative vitreoretinopathy (FEVR) is an inherited vitreoretinopathy. This study aimed to analyze the ocular phenotypes and systemic features of patients with CTNNB1 mutations. Methods Whole exome sequencing was performed in the probands, and Sanger sequencing was used to verify the mutations and perform segregation analysis in the available family members. A luciferase assay was used to assess the effect of the mutant β-caten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The condition can manifest in various clinical syndromes, ranging from mild peripheral avascularity with normal visual acuity to severe retinal detachment, ultimately leading to blindness. FEVR can associate with intellectual disabilities [1][2] , and is reported to be autosomal dominant (AD), autosomal recessive inheritance (AR), or X-linked inheritance trait, and genetically associated with the genes of FZD4 [3] , LRP5 [4] , TSPAN12 [5] , NDP [6] , KIF11 [7] , ZNF408 [8] , RCBTB1 [9] , CTNNB1 [10] , and JAG1 [11] . While point gene variations in nucleic acids have commonly been implicated in the disease, recent studies have also identified copy number variants (CNVs) as contributing factors.…”
Section: Introductionmentioning
confidence: 99%
“…The condition can manifest in various clinical syndromes, ranging from mild peripheral avascularity with normal visual acuity to severe retinal detachment, ultimately leading to blindness. FEVR can associate with intellectual disabilities [1][2] , and is reported to be autosomal dominant (AD), autosomal recessive inheritance (AR), or X-linked inheritance trait, and genetically associated with the genes of FZD4 [3] , LRP5 [4] , TSPAN12 [5] , NDP [6] , KIF11 [7] , ZNF408 [8] , RCBTB1 [9] , CTNNB1 [10] , and JAG1 [11] . While point gene variations in nucleic acids have commonly been implicated in the disease, recent studies have also identified copy number variants (CNVs) as contributing factors.…”
Section: Introductionmentioning
confidence: 99%